Zimbardo’s Time Perspective and Binge Drinking Patterns in Alcohol Consumption among Black African International University Students in China - Nguni, Alice; Lyu, Houchao; Paul, Ravi; Li, Xiaobao (UI Scholars Hub, 2023)
Addictive alcohol use among university students in China is a growing public health concern. This study examines Binge drinking and time perspective among Black African students from Southwest University in China. While the Time Perspective focuses on the past, present, or future that may predict alcohol abuse, its relationship with Binge drinking among Black Africans in China remains unexplored. Among 370 participants, data was gathered using the Time Perspective Inventory and Alcohol Use Disorders Identification Test. Regression analysis indicated a positive association between the present (fatalistic, hedonistic), future, and past-positive TP and binge drinking, while the Future time frame showed an indirect correlation. Age and Sex also correlated with Past Positive and Future time frames. These findings might inform interventions to mitigate heavy drinking on campuses, given students' concerns about future uncertainties.